Worrying About Leadership: Is It a Liability or an Advantage for Leadership of Women and Men? - Karakulak, Arzu; Başkurt, Ayşe Burçin; Koseoglu, Gamze; Aycan, Zeynep (Frontiers in Psychology, 2022)
Worries about leadership (WAL) is a new construct tapping worries an individual may feel about possible negative consequences of accepting a leadership role. Three studies investigate how WAL is associated with men’s and women’s willingness for leadership and their perceived leadership potential rated by others. The first is a laboratory study on 328 participants shows that WAL is negatively associated with women’s willingness for leadership, while it was not related to that of men’s. The second study, which is a field study with multilevel nested data from 429 employees and 101 supervisors, reveals that male subordinates are more likely to receive a favorable judgment of leadership potential by their supervisors when their WAL increases, while female subordinates’ WAL isirrelevant to this judgment. The final study, which is an experimental study on 122 supervisors shows that supervisors view hypothetical male leadership candidates with high WAL as having higher warmth and lower competence (than those with low WAL), which both mediats the effect of WAL on judgments of their leadership potential made by the participants. Even though participants also view female candidates with high WAL as warmer, this doesnot evoke higher perceptions of leadership potential. Implications for increasing gender parity in leadership are discussed.